2003
DOI: 10.1002/ijc.11534
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model to optimize dose scheduling of multimodal radioimmunotherapy and chemotherapy: Effects of p53 expression

Abstract: Several reports have appeared on the use of combined radioimmunotherapy (RAIT) and chemotherapy. The choice of drug to use with RAIT and how to space the two treatments has not been completely addressed. Because every patient's cancer presents with a specific molecular phenotype, we hypothesized that it may be necessary to tailor therapy based on specific gene expression. We addressed how the form of expression of a single gene, the p53 tumor suppressor, would impact the choice of agents, as well as sequence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Different parameters such as drug accumulation, the level of topoI-DNA complex formation, the expression and activity of topoI, and the level of Mdr-1, Bcl-2, and Bax were not found to be predictive for the sensitivity to topoI inhibitors or were disputed (Goldwasser et al, 1995;Davis et al, 1998;Schmidt et al, 2001;Blumenthal et al, 2004). This also applies to p53, for which we showed that it determines the sensitivity of glioma cells to TPT (Tomicic et al, 2005b).…”
mentioning
confidence: 68%
“…Different parameters such as drug accumulation, the level of topoI-DNA complex formation, the expression and activity of topoI, and the level of Mdr-1, Bcl-2, and Bax were not found to be predictive for the sensitivity to topoI inhibitors or were disputed (Goldwasser et al, 1995;Davis et al, 1998;Schmidt et al, 2001;Blumenthal et al, 2004). This also applies to p53, for which we showed that it determines the sensitivity of glioma cells to TPT (Tomicic et al, 2005b).…”
mentioning
confidence: 68%
“…4 The importance of empirically determining the administration sequence of RIT and chemotherapy is not a new concept. 33,34 In fact, earlier in vitro studies, with four ovarian cell lines and four drugs that included carboplatin, demonstrated clear differences between the drugs and their combination with 90 Y RIT. Interestingly, in the hierarchical rating of the four drugs, carboplatin always placed in the worst combination.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing a panel of glioma cell lines, no influence of p53 on cell death induced by topotecan was observed (13). In contrast, in ovarian cancer cells that regained p53 function upon p53 transfection, a protective effect of p53 on topotecan treatment was found (14). The reason for the observed p53-mediated protection remained unclear.…”
Section: Introductionmentioning
confidence: 99%